Impact of physical activity on all-cause mortality in individuals with non-cystic fibrosis bronchiectasis - Kim, Sang Hyuk; Choi, Hayoung; Han, Kyungdo; Jung, Jin-Hyung; Yang, Bumhee; Lee, Hyun (Frontiers in Medicine, 2025)
BackgroundLittle information is available regarding whether active physical activity lowers mortality risk in individuals with bronchiectasis.MethodsWe used the Korean National Health Insurance Service database from 2010 to 2016 to evaluate the association between changes in physical activity and mortality risk in individuals with bronchiectasis. Of 552,510 individuals with newly diagnosed bronchiectasis, we enrolled 165,842 individuals who had two consecutive health examinations before and after bronchiectasis diagnosis, within two years, as the study aimed to measure changes in exercise habits between the two time points. Active physical activity was defined as engaging in moderate- or vigorous-intensity physical activity at least once a week, either before or after bronchiectasis diagnosis. The outcome measure was all-cause mortality.ResultsDuring a mean follow-up of 6.2 ± 2.1 years, 10,535 (6.4%) individuals with bronchiectasis died. Individuals with bronchiectasis who were physically active exhibited a lower mortality rate than those who were physically inactive. Mortality reduction was particularly evident in the exercise maintainers group (aHR [adjusted hazard ratio] = 0.69, 95% confidence interval [CI] = 0.64–0.74) and individuals with physical activity ≥1,000 metabolic equivalent of task-min per week (aHR = 0.73, 95% CI = 0.70–0.77) compared to those who were physically inactive.ConclusionEngaging in active physical activity is associated with a decreased risk of mortality in individuals with bronchiectasis.